2020
DOI: 10.21203/rs.3.rs-36052/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combination of SB431542, Chir9901, and Bpv as a novel supplement in the culture of umbilical cord blood hematopoietic stem cells

Abstract: Background: Small molecule compounds have been well recognized for their promising power in generation, expansion and maintenance of embryonic or adult stem cells. The aim of this study was to identify a novel combination of small molecules in order to optimize the ex vivo expansion of umbilical cord blood derived-CD34+ cells. Methods: Considering the most important signaling pathways involved in the self-renewal of hematopoietic stem cells, CB-CD34+ cells were expanded with cytokines in the presence of seven … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…We evaluated the profile of HSPC content post 7 days of treatment with 0.1, 1, and 10 µM doses of HSMs selected on UCB experiment. We used the previously tested compound bpV(Hopic) 21 as a positive control. HSPC analysis evaluated with flow cytometry gating strategy (Figure 3A) indicated that different doses of HSMs (10 µM for p300/CBP inhibitor VI, 0.1 µM for 2‐APB, 0.1 µM for BML‐260, 1 µM for TAME, 0.1 µM for Meisi‐1, and 1 µM for Meisi‐2) were the most effective for HSPC expansion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the profile of HSPC content post 7 days of treatment with 0.1, 1, and 10 µM doses of HSMs selected on UCB experiment. We used the previously tested compound bpV(Hopic) 21 as a positive control. HSPC analysis evaluated with flow cytometry gating strategy (Figure 3A) indicated that different doses of HSMs (10 µM for p300/CBP inhibitor VI, 0.1 µM for 2‐APB, 0.1 µM for BML‐260, 1 µM for TAME, 0.1 µM for Meisi‐1, and 1 µM for Meisi‐2) were the most effective for HSPC expansion.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we screened previously uncharacterized 35 putative hematopoietic small molecules (HSMs) along with previously reported ones (Alexidine Dihydrochloride, 16 Garcinol, 17 ‐CHIR‐99021, 18 Stemregenin‐1, 19 AMD3100, 20 Bpv(HopiC), 21 EX‐527, 22 SB203580, 23 Bio 24 on mPB and UCB HSCs to determine the effective HSMs and/or HSM cocktail for the development of serum‐free chemically defined medium, which will enhance human HSPC expansion. Through cell cycle kinetics modulation, we discovered that several new small molecules are promising for both human mPB‐ and UCB‐derived HSC ex vivo expansion.…”
Section: Introductionmentioning
confidence: 99%